(untitled) (Simbiótica. Revista Eletrônica, 2022)
This article presents a dialectic between the historiographical production of Aby Warburg and a poetic production of Fernando Pessoa based on an unusual theme: the diligent study of astrology in the midst of their artistic research. Furthermore, both consider changing the parameter of aestheticism and representation in favour of the study of art as a science of expression. It is therefore of interest here to reassess the concrete relevance of astrology, with its celestial, terrestrial and, above all, graphic landscapes for this epistemological turn. Keywords: Aby Warburg; Fernando Pessoa; Astrology; Expression.